2013
DOI: 10.1080/02699931.2012.689756
|View full text |Cite
|
Sign up to set email alerts
|

Do sadness-primes make me work harder because they make me sad?

Abstract: This experiment sought to clarify the potential role of emotional feelings in the systematic impact of implicitly processed affective stimuli on mental effort mobilisation. Participants worked on an attention task during which they were primed with suboptimally presented happiness versus sadness expressions. Before the task, half the participants received a cue for the possible affective influence of "flickers" to be presented during the task. This manipulation usually reduces the impact of conscious feelings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
39
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 19 publications
9
39
2
Order By: Relevance
“…Several studies have supported this systematic impact of implicitly processed affect primes on effort-related cardiovascular response in cognitive tasks (e.g., Chatelain and Gendolla, 2015;Gendolla and Silvestrini, 2011;Lasauskaite et al, 2013). The present research applied a similar logic to explain how the aging stereotype can influence effort mobilization.…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…Several studies have supported this systematic impact of implicitly processed affect primes on effort-related cardiovascular response in cognitive tasks (e.g., Chatelain and Gendolla, 2015;Gendolla and Silvestrini, 2011;Lasauskaite et al, 2013). The present research applied a similar logic to explain how the aging stereotype can influence effort mobilization.…”
Section: Introductionmentioning
confidence: 63%
“…Also in our previous studies on affect priming, we have only sometimes found prime effects on subjective demand ratings (e.g., Gendolla and Silvestrini, 2011;Lasauskaite et al 2013, Lasauskaite Schüpbach et al, 2014Silvestrini and Gendolla, 2011b), or subjective effort (e.g., Chatelain and Gendolla, 2015). Other studies revealed the expected effort effects without significant effects on these self-report measures (e.g., .…”
Section: Discussionmentioning
confidence: 99%
“…The discrepancy between both results is not surprising. There was no evidence that our affect priming procedure induced conscious emotional feelings and thus nothing that could be corrected in the Lasauskaite et al () study. But apparently, the affect primes influenced experienced task demand in the Lasauskaite Schüpbach () experiment, i.e., an experience that could be corrected.…”
Section: Empirical Evidencementioning
confidence: 69%
“…Moreover, it is of note that informing participants about the possible manipulation of their emotional feelings (rather than subjective demand) had not attenuated the prime effects in the earlier‐discussed study by Lasauskaite et al (). The discrepancy between both results is not surprising.…”
Section: Empirical Evidencementioning
confidence: 74%
See 1 more Smart Citation